Effect of Incorporating Bay Leaves in Cookies on Postprandial Glycemia, Appetite, Palatability, and Gastrointestinal Well-Being - Khan, I.; Shah, S.; Ahmad, J.; Abdullah, A.; Johnson, Stuart (American College of Nutrition, 2017)
© 2017 American College of Nutrition. Background: Previous studies of patients with type 2 diabetes showed that capsules containing 1, 2, and 3 g of bay leaves lower fasting blood glucose, triglycerides, low-density lipoprotein cholesterol, and total cholesterol concentrations after 30 days of treatment. However, the acute effect of bay leaves on postprandial glycemic and appetite responses has not yet been determined. Objective: The objective of this study was to determine the effect of cookies containing different doses of bay leaves on postprandial glycemia, appetite, palatability, and gastrointestinal well-being in healthy subjects. Methods: In a randomized crossover study, 20 subjects consumed 3 test foods each providing 50 g of available carbohydrates. The test foods were provided as breakfast, 1–2 weeks apart, and were control cookies (CC) made from 100% wheat flour, cookies containing 3% (w/w) bay leaf powder (B3), and cookies containing 6% (w/w) bay leaf powder (B6). Blood glucose, subjective appetite, and gastrointestinal well-being were assessed at fasting and postprandially for 2 hours. Palatability of the test cookies was measured using 9-point hedonic scale. Results: There was a significant effect of time (p < 0.001), treatment (p = 0.033), and Time × Treatment interaction (p = 0.001) on postprandial blood glucose concentrations. Post hoc pairwise comparison showed that blood glucose concentration was significantly reduced by B6 compared to CC at 30 and 45 minutes (p = 0.014 and p = 0.010, respectively). However, there were no significant differences (p = 0.411) in blood glucose incremental areas under the curves (iAUCs) among the treatments. No significant effect on any of the appetite parameters was observed among the treatments. All of the cookies were rated as acceptable and subjects did not report any gastrointestinal discomfort. Conclusion: In conclusion, the results indicate that cookies containing bay leaf powder at 6% (w/w) incorporation level provides a palatable product that induces a reduced glycemic response.